Pemberdayaan UMKM Melinjo Melalui Inovasi Produk Keceprek Rasa Cokelat di Desa Dahu - Faiz Muzakki; Helga Sri Asih; Mohamad Ikrom rasid; Erhnes Tria Anabe; Ilham Arifin; Nadia Sari; Resta Olimpia; Qory Meidina Izria; Tiana Bela; Fitriana Ramadanti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Small and medium-sized enterprises (SMEs) have long been recognized as a vital driver of economic growth, particularly in rural areas where access to large-scale industries is limited. In Dahu Village, the community relies on local products such as melinjo as one of the main sources of livelihood. However, despite the potential of melinjo-based products, business development has been constrained by limited innovation, low product diversification, and weak marketing strategies. These challenges hinder the competitiveness of local SMEs in wider markets, especially in appealing to younger consumers who often prefer modern and innovative products. To address these challenges, the 2025 Student Work Study Program (KKM) conducted by the University of Bina Bangsa implemented a community empowerment project aimed at enhancing the capacity of SMEs in the melinjo sector. The program introduced the development of an innovative product, namely chocolate-flavored keceprek, a melinjo-based snack with a unique taste and higher market value. The initiative not only focused on product innovation but also provided comprehensive support in production techniques, hygienic and attractive packaging, logo and banner design, as well as digital marketing strategies tailored to rural entrepreneurs. The results of the activity highlight that even a relatively simple innovation can significantly increase product appeal, improve branding, and create new market opportunities. Early feedback indicated that chocolate-flavored keceprek products successfully attracted interest from younger consumers, demonstrating the importance of innovation in maintaining the relevance of traditional products. Furthermore, the project functioned as a collaborative platform where students and local communities worked together in applying entrepreneurial concepts to local potential. This synergy not only contributed to improving the competitiveness of SMEs in Dahu Village but also encouraged sustainable economic development in rural areas through innovation, creativity, and digital-based marketing.